Migraine severity, disability, and duration: Is a good diet quality, high intake of phytochemicals and polyphenols important? - Bakırhan, Hande; Pehlivan, Merve; Uyar Cankay, Tuğba; Kocak, Mehmet (Frontiers in Nutrition, 2022)
Objectives: Dietary pattern may be the determinant of migraine prognosis through various mechanisms such as systemic inflammation, vasodilation, cerebral glucose metabolism and mitochondrial dysfunction. This study was conducted to examine the relationship of the symptoms and signs of migraine with dietary polyphenols and the phytochemical intake and the quality of the diet. Methods: Individuals (n=90), who were admitted to the headache outpatient clinic due to the diagnosis of episodic migraine, underwent physical examination by a neurologist. Migraine characteristics were assessed using the Migraine Disability Assessment Questionnaire and the Visual Analogue Scale. The Healthy Eating Index-2015 (HEI-2015) was used to evaluate the diet quality of individuals, and the Phytochemical Index developed by McCarty was used to determine the dietary intake of phytochemicals. Phenol-Explorer version 3.6 and the USDA Database for the Flavonoid Content of Selected Foods-Release 3.3 were used to calculate the dietary polyphenol intake. Results: Migraine severity was negatively correlated with the intake of phytochemicals and good diet quality (r=-0.37, p=0.0003; r=-0.37, p=0.0003, respectively), and with the intake of phenolic components flavanones (r=-0.27, p=0.01) and lignans (r= -0.27, p=0.01). With respect to the food groups; migraine severity was found to be inversely correlated with the total phenol intake from olive oil, oil, and fruits (r=-0.26, p=0.01; r=-0.21, p=0.04; r=-0.24, p=0.02, respectively), and the flavonoid intake from olive oil, oil, fruits, and vegetables (r=-0.26, p=0.01; r=-0.26, p=0.01; r=-0.35, p=0.0007; r=-0.22, p=0.04, respectively). Strikingly, fruit flavanone intake was correlated with low migraine severity (r=-0.39, p=0.0002), and fruit flavanol intake was correlated with low migraine disability (r=-0.21, p=0.04). Conclusion: A high-quality diet rich in phytochemicals and polyphenols (especially flavanones and lignans) is associated with low migraine severity. Lower intake of phenols and flavonoids from vegetable oil, olive oil, fruits and vegetables were associated with more severe migraine attacks. Examination of migraine characteristics and dietary pattern together with phytochemical and polyphenol intake may guide the development of dietary strategies to be used in migraine patients.